Functional outcome of macular edema in different retinal disorders. (September 2015) - Tomkins-Netzer, Oren; Ismetova, Filis; Bar, Asaf; Seguin-Greenstein, Sophie; Kramer, Michal; Lightman, Sue
Abstract: Macular edema accompanies many ocular pathologies, affecting visual function and is an important factor in treatment decisions and disease outcome. Though visual acuity is commonly used to evaluate patient vision it does not always provide a complete estimate of their visual abilities or reflect their own visual perception. Furthermore, different pathologies result in macular edema causing a variable effect on visual function, related to the rate of fluid accumulation and accompanying ocular changes. Use of complementary visual function tests, such as retinal contrast sensitivity on microperimetry and reading speed provide additional information that can be used to evaluate patients and assist in treatment choices. Here we explore the effect of macular edema on visual function in different retinal pathologies, namely diabetic retinopathy, retinal vein occlusion and uveitis, examine its influence on the various vision tests and discuss the factors underlying this variable response. Graphical abstract: